Tinjauan Hukum Persaingan Usaha Terhadap Konflik Antara Taksi Konvensional dan Taksi Online - Melisa Safitri (Universitas Bandar Lampung (UBL), 2015)
The conflict between the Conventional Cab’s drivers and Online Cab’s drivers happened as the form of seizing their revenue coming from the passengers. The conflict exalation heated as the profit displacement moved from the conventional one into the online. This paper is a Normatif research using both of the statute approach and also the conceptual approach. The data collected from the literature studies, focusing on reading and analysis primary and secondary materials. The research result shows that the basic caused of this conflict is there is no statute focusing on the online cab’s regulation, so that the regulation dedicated to the conventional one is more complicated than the online one. This is why the price of the transportation service from the online cab is a lot cheaper than the conventional one and causing most of the conventional’s passengers are prefer using the online cab for now. There is no indication of a cut throat competition done by the online cab. The government should arrange a new regulation dedicated to the online cab about the detail of requirements as same as in regulating the conventional cab. Online cab can not be blamed as it meets the society’s needs of a kind of transportation with its efficiency as the part of science and technology growth.